PERAN FILOSOFI BUDAYA BATAK TOBA DALAM DUNIA PENDIDIKAN - Agnes Novianti Permata Sari Hutahaean; Winarti Agustina (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
Batak Toba ethnic group has a cultural philosophy in guiding their lives. To achieve this philosophy, they carry out education because they are aware of education constituting the rung to achieve the philosophy. This study aims to examine the philosophy of Toba Bataknese culture to shape the mindset of the Batak Toba ethnic group about the importance of education. The study design is qualitative one with the descriptive approach. The techniques of collection data are carried out through library research as a literature material that can present data and be accompanied with supporting document constituting an important reference in this study. The result of the study shows that the cultural philosophy of the Batak Toba ethnic group is intended to the power and the effort to achieve sahala ownership and understanding on rajawi man. The Content of sahala includes hagabeon (having children), hasangapon (honor achieved through education, and experience), and hamoraon (wealth). And the concept of a Rajawi man is a freedom of self-development, freedom to build a vision and to pursue life ambitions. The values of hagabeon, hasangapon, hamoraon and life ambition can be achieved by undergoing education in order to form a good mindset and to gain knowledge. So, it is unsurprising that the education on ethnic Batak is quite developing and advanced.